A study on the effects of flyover construction on traffic flow the case of Metro Manila - Quezon, Emer T.
The study seeks to present the effects of the flyover construction on traffic flow within the selected area in Metro Manila adopted the "with" and "without" case at-already completed flyover construction. These tow views were categorically differentiated by bringing up several viewpoints that will evaluate the effectiveness of the flyover construction. THe said viewpoints are the following, to wit: 1. what will happen if the flyover was not constructed?, 2. What is the current traffic situation? 3. what are the problems being experienced by travelers brought about by this setup?, and lastly, 4. is this flyover properly utilized? These are some of the many questions raised by cause-oriented groups which this research attempts to clarify. The comparative analysis concerning those viewpoints on "With" and "without" case at-already completed flyover construction was based on a basic concept of the study. This basic concept is the use of the travel time and delay as the measure for evaluation. The evaluation measure is used in applying the mathematical model formulated by DOHERTY and CATLING. This model would be used for "with" case of flyover construction to compare with the observed values by applying statistical analysis to test the model. After the test of the model, due validation of the results and the same model would be applied for "without" case at-already completed flyover construction to provide for a comparative analysis. A research paper such as the present work is justified by the need to present a more profound, truthful and understandable presentation of the subject. More so, because there have not been many studies conducted tackling this line of endeavor in the Philippine setting, maybe due to its very recent age and short experience how these flyovers work efficiently.